Distribution, habitat suitability, natural history, bite report, and medical importance of the Asian tarantula Chilobrachys spp. - Mondal, Ayan; Das, Shouvik; Mukherjee, Subha Shankar; Saha, Shubhajit (Frontiers in Arachnid Science, 2025)
The Chilobrachys tarantula, a genus of Old-World tarantulas, is known for its unique behavior and venomous bites, which have varying effects on humans. This research provides a comprehensive overview of Chilobrachys species distribution, bite incidents, and medical treatment based on bioclimatic modeling and clinical case reports. Chilobrachys species thrive in regions with moderate daily temperature ranges (−7.9°C to 43.3°C), stable climates, and sufficient precipitation (0 mm to 2,325 mm), particularly in Southeast Asia. Key bioclimatic variables such as maximum temperature of the warmest month (BIO5) and precipitation during both warm and cold months (BIO18, BIO19) significantly influence species distribution. Field data from 24 confirmed Chilobrachys bites reveal that most incidents occur between April and July, with bite symptoms ranging from severe localized pain, swelling, and necrosis to systemic effects like fever and hemoglobinuria. Case studies demonstrate the cytotoxic effects of Chilobrachys venom, leading to complications such as cellulitis, necrosis, and compartment syndrome, particularly in untreated or delayed cases. Medical reports indicate that treatment involves immediate first aid (RICE protocol), pain management, antihistamines for allergic reactions, and antibiotics to prevent secondary infections. In severe cases, surgical intervention is required for necrosis and compartment syndrome management. Bioclimatic and clinical data emphasize the need for public awareness, healthcare training, and early intervention to mitigate the risks associated with Chilobrachys bites. This research provides crucial insights into the ecological and medical aspects of these tarantulas, aiding in the prevention and management of envenomation cases.